Effect of white tea consumption on the heart of type 2 diabetic rats - Teixeira, Nelson Augusto Ferreira (2014)
According to the World Health Organization (WHO), diabetes mellitus (DM) is the ninth leading cause of death worldwide, and 80% of those deaths are due to cardiovascular disease. The heart functions as a pump with a continuous need for energy and therefore is very susceptible to metabolic and/or oxidative alterations. It is well known that DM induces important metabolic alterations that result in increased oxidative stress (OS). Many medicinal plants are used worldwide to counteract the deleterious effects of DM. Although it is a fact that some harmful characteristics of DM are indeed ameliorated, the mechanisms by which medicinal plants improve the body response to this disease remain unknown. In the last few years, scientific studies concerning the effect of tea consumption, one of the most consumed beverages in the world, significantly increased. There are several works reporting that tea consumption may improve heart function in diabetic individuals. However, much of these studies are focused in green tea (GT) and most of the mechanisms of tea action remain unknown. Herein, we hypothesized that the consumption of the less studied tea, the white tea (WTEA), improves the heart functioning of diabetic individuals. To test our hypothesis, we used a STZ-induced Type 2 diabetes (T2D) rat model. The animals were divided in 3 groups: control, STZ-induced T2D (STZ) and WTEA drinking STZ-induced T2D rats (STZ+WTEA). Before sacrifice, the animals were subjected to a glucose tolerance and insulin sensitivity tests. Heart lipid peroxidation and protein oxidation were determined. Glucose, lactate, alanine and acetate contents in the hearts were quantified. mRNA expression levels of glucose transporter-1 (GLUT1), lactate dehydrogenase (LDH) and monocarboxylate transporter 4 (MCT4) were also determined, as well as LDH activity, in the heart. Our results show that WTEA consumption restored insulin sensitivity and glucose tolerance in STZ-induced T2D rats. Besides, WTEA consumption restored lipid peroxidation to control values and decreased protein oxidation in hearts from STZ-induced T2D rats. Finally, STZ-induced T2D rats presented an impaired glycolysis that appears to be ameliorated by WTEA consumption. In these processes, regulation of GLUT1 and LDH activity proved to be essential in the protective effect shown by WTEA consumption. More studies are needed to confirm the beneficial effects of WTEA consumption but our results provide clear evidence that WTEA ingestion can be a good, safe and inexpensive strategy to decrease the deleterious effects of T2D to the heart.